PENGARUH KOMPENSASI, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA GURU TIDAK TETAP (GTT) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Parmin Parmin (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
This study aims to influence the variables that affect the performance of non-permanent teachers in kindergarten level in Alian District. The variables studied include compensation, competence and work motivation that is suspected to have an effect on the performance of non- permanent teacher in kindergarten level in Alian sub-district through job satisfaction variable. The population in this research is the kindergarten teacher in kindergarten level in Alian Subdistrict which is 50 people. Sampling with sampling method saturated as many as 50 people. Data collected by questionnaire. Data analysis used is instrument validity and reliability test, classic assumption test, hypothesis test, correlation analysis and path analysis. The results showed that compensation had no significant effect on job satisfaction. Compensation has a positive and significant effect on performance. Competence has no significant effect on job satisfaction. Competence has a positive and significant effect on performance. Motivation has a positive and significant effect on job satisfaction. Motivation has no effect on performance. Job satisfaction has no effect on performance. The result of the coefficient of determination of substructure I of 42,4% indicates the influence of meaningful relationship between compensation, competence and motivation to job satisfaction of GTT Kindergarten level in Alian Subdistrict. The result of the coefficient of determining substructure II is 44,6% showing the influence of compensation, competence and motivation through job satisfaction on GTT performance of kindergarten level in Alian Subdistrict.